Severe dapsone hypersensitivity syndrome in a child - So Yoon Choi; Ho Yeon Hwang; Jung Hyun Lee; Jae Sun Park; Min Soo Jang (Korean Pediatric Society, 2013)
Dapsone (4,4'-diaminodiphenylsulfone, DDS), a potent anti-inflammatory agent, is widely used in the treatment of leprosy and several chronic inflammatory skin diseases. Dapsone therapy rarely results in development of dapsone hypersensitivity syndrome, which is characterized by fever, hepatitis, generalized exfoliative dermatitis, and lymphadenopathy. Here, we describe the case of an 11-year-old Korean boy who initially presented with high fever, a morbilliform skin rash, generalized lymphadenopathy, hepatosplenomegaly, and leukopenia after 6 weeks of dapsone intake. Subsequently, he exhibited cholecystitis, gingivitis, colitis, sepsis, aseptic meningitis, disseminated intravascular coagulation, syndrome of inappropriate antidiuretic hormone secretion, pneumonia, pleural effusions, peritonitis, bronchiectatic changes, exfoliative dermatitis, and acute renal failure. After 2 months of supportive therapy, and prednisolone and antibiotic administration, most of the systemic symptoms resolved, with the exception of exfoliative dermatitis and erythema, which ameliorated over the following 4 months. Agranulocytosis, atypical lymphocytosis, aseptic meningitis, and bronchiectatic changes along with prolonged systemic symptoms with exfoliative dermatitis were the most peculiar features of the present case.